Somatic gene mutations in the motor cortex of patients with sporadic amyotrophic lateral sclerosis - González-Velasco, Óscar; Parlato, Rosanna; Yılmaz, Rüstem; Decker, Lorena; Menge, Sonja; Freischmidt, Axel; Yang, Xiaoxu; Tulasi, Nikshitha; Brenner, David; Andersen, Peter M; Forsberg, Karin M E; Schlachetzki, Johannes C M; et al. (Brain, 2026)
Amyotrophic lateral sclerosis (ALS) is characterized by the progressive degeneration of cortical and spinal motor neurons. Mendelian germline mutations often cause familial ALS (fALS) but only approximately 10% of sporadic ALS cases (sALS).We leveraged DNA and single-cell RNA sequencing data from autopsy tissue to explore the presence of somatic mosaic variants in sALS cases.Deep targeted panel sequencing of known ALS disease genes in motor cortex tissue revealed an enrichment of low allele frequency variants in sALS, but not in fALS with an identified monogenic cause. In silico analysis predicted increased pathogenicity of mosaic mutations in various known ALS mutational hot-spots. In particular, we identified the somatic FUS variant p.E516X, located in an established hotspot for germline ALS mutations, which leads to nucleo-cytoplasmic mislocalization and aggregation typical for ALS FUS pathology. Additionally, we performed somatic variant calling on single-cell RNA-sequencing data from sALS tissue and revealed a specific accumulation of somatic variants in excitatory neurons, reinforcing a neuron-autonomous disease initiation.Collectively, this study indicates that somatic mutations within the motor cortex, especially in excitatory neurons, may contribute to sALS development.
Erstmals veröffentlicht: 11. Dezember 2025
Gesehen am 02.03.2026